Synthesis of 3-phenyl-4-styryl and 3-phenyl-4-hydroxy coumarins - Shaima Ismaeel (College of Education for Pure Sciences, 2008)
ABSTRACT In this paper the synthesis of substituted 3-phenyl-4-styryl and 3-phenyl-4-hydroxy coumarins is reported. The substituted benzaldehydes were treated with 2-hydroxy acetophenone to give the corresponding chalcone, the hydroxy chalcone then reacted with phenyl acetic acid in pyridine and phosphorus oxychloride to give the intermediates esters, which then cyclized to 3-phenyl-4-styryl coumarins by their reaction with potassium hydroxide. Substituted methyl salicylate were converted to the esters by their reaction with phenyl acetic acid and phosphorous oxychloride in pyridine, followed by cyclization with potassium hydroxide in pyridine to give 3-phenyl-4-hydroxy coumarins. The structures of the synthesized compounds were established by physical and spectral methods.